Media Edukasi Video Animasi terhadap Pemahaman Mahasiswa Tuna Rungu pada Mata Kuliah Psikologi ABK - Sukmawati, Bhennita; Citra, Nostalgianti; Yulinda, Khusna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the understanding of deaf students towards abnormal psychology courses using animated video educational media. This research uses descriptive qualitative research method with the type of case study research. The technique of taking research subjects using purposive sampling technique. The data analysis technique was carried out by data reduction, data categorization, synthesis and ended by compiling working hypotheses. Test credibility by using triangulation. The results showed that subjects A and B were; 1. increase understanding, which is marked by being able to explain the material briefly and precisely 2. Able to explain words that are not understood 3. Able to ask and answer questions. In conclusion, learning using animated video educational media can have a good impact on deaf students. Learning using animated videos can improve and develop students' abilities in the cognitive, affective and psychomotor domains. Keywords: Affective and Psychomotor, Animation Media, Deaf